2019
DOI: 10.1111/zph.12658
|View full text |Cite
|
Sign up to set email alerts
|

Coxiella burnetiiseroprevalence in unvaccinated veterinary workers in Australia: Evidence to support Q fever vaccination

Abstract: Q fever (caused by Coxiella burnetii) is a serious zoonotic disease that occurs almost worldwide. Occupational contact with animals increases the risk of exposure, and Q fever vaccination is recommended for veterinary workers in Australia. This study aimed to investigate C. burnetii seroprevalence among unvaccinated veterinary workers in Australia and determine factors associated with a positive serological result. During 2014 and 2015, convenience sampling at veterinary conferences and workplace vaccination c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 46 publications
4
10
1
Order By: Relevance
“…Overall, three (2%) out of the 147 unvaccinated AWRs in this cohort self-reported having been medically diagnosed with QFD. This finding is similar to what was found in a study on Australian veterinary workers by Sellens et al [ 58 ], where 2% (4/192) of the cohort reported having QFD, but lower in comparison to another study of Australian cat breeders in which 6% (7/123) of the study population reported having had medically diagnosed QFD [ 62 ]. In all three studies, the level of QFD is substantially higher than the Australian annual notification rate of 0.002% [ 48 ].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Overall, three (2%) out of the 147 unvaccinated AWRs in this cohort self-reported having been medically diagnosed with QFD. This finding is similar to what was found in a study on Australian veterinary workers by Sellens et al [ 58 ], where 2% (4/192) of the cohort reported having QFD, but lower in comparison to another study of Australian cat breeders in which 6% (7/123) of the study population reported having had medically diagnosed QFD [ 62 ]. In all three studies, the level of QFD is substantially higher than the Australian annual notification rate of 0.002% [ 48 ].…”
Section: Discussionsupporting
confidence: 88%
“…This enabled a detailed analysis of the respective data sets to identify potential risk factors associated with seropositivity and having received Q fever vaccination. The 6.1% seroprevalence observed in the current study is lower than the 19% C. burnetii seroprevalence reported for a cohort of unvaccinated Australian veterinary workers, where increasing exposure to ruminants was identified as a significant risk factor for seropositivity [ 58 ]. International studies of livestock veterinarians have reported seroprevalence for C. burnetii as high as 65.1% [ 67 ].…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…These reactions necessitate costly pre-vaccination serologic screening and intradermal skin testing which delays vaccination (7)(8)(9). Surveys for anti-C. burnetii antibodies in at-risk populations, particularly those who work in animal husbandry and veterinary fields, reported seroprevalence rates of 18.3-45.13% (10)(11)(12). The high seroprevalence rates show that these groups that would most benefit from vaccination also bear the greatest risk of hyper-reactive responses.…”
Section: Introductionmentioning
confidence: 99%